Pelatihan Pembelajaran Al-Quran Dengan Metode Qiro’ati di TPQ Al Amin Desa Bondrang - Muhammad Irkham Firdaus Firdaus; Rif'at Husnul Ma'afi; Wildan Taqiyuddin; Yusuf Alayda Hafidz; Muhammad Syaifuddin (Kreativasi : Journal of Community Empowerment, 2023)
Community Service is carried out by lecturers and students located in Bondrang village, Sawoo sub-district at TPQ Al-Amin, where there are concrete problems, namely TPQ teaching human resources, where there is a lack of potential for young people to teach the Koran at TPQ and the majority of young people in the village has worked and helped families in gardening or animal husbandry, in addition to that the teacher's lack of understanding of the Qiro'ati method, so the teaching method was less effective, and made students less interested in the method. This PKM uses the method of socialization, counseling, training, and mentoring. This activity was carried out by providing training in teaching the Qiro'ati method to teachers and students, as well as attracting new teaching staff from local youth. And made textbooks on the Qiro'ati method, Mutaba'ah (Assistance) books for Santri Parents, and development of the TPQ Al-Amin curriculum.